Pengaruh Pelatihan SBAR Role-Play terhadap Skill Komunikasi Handover Mahasiswa Kebidanan - Kharisah Diniyah (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
Effective communication is a component in patient safety standards, one of which is implemented in the handover activity. One of the widely used standard is the SBAR (Situation Background Assessment Recommendation). This study uses a quasi experiment research design with a one-group pre-post test design. Respondents in this study are 29 students from 2nd and 3rd year students of midwifery who are conducting obstetrics clinical practice. The data collection is done by observation, and analyzed using the Wilcoxon Match Pairs Test. This study indicates that effective communication role play using the SBAR method can improve effective communication skills at the time of handover and will give better results if done using real cases. So SBAR communication methods can be used as an effective communication standard that can be applied at the time of handover.